Assertive dominance and rhetorical integration in tiktok affiliate discourse: a pragmatic-rhetorical study of digital persuasion - Dicky Pramana Putra; Muhammad Rohmadi (Indonesian Institute for Counseling, Education and Theraphy, 2026)
This study examines the pragmatic strategies of digital persuasion in TikTok Affiliate content, addressing a gap in speech act research on creator-based advertising discourse. A corpus of 166 utterances from 15 videos by three Indonesian creators was analyzed using Searle's (1976) taxonomy and Aristotle's rhetorical framework. Findings reveal three key patterns: (1) assertive speech acts dominate (72.89%), particularly 'mentioning specifications' (38.55%), reflecting a 'trust-first' persuasion logic; (2) logos (60.24%), pathos (25.90%), and ethos (13.86%) operate complementarily within single utterances, not in separate segments; and (3) a consistent illocutionary-rhetorical matrix shows that 'claiming' is paradoxically grounded in ethos (50%) rather than logos, indicating that personal credibility substitutes objective data in this genre. This pragmatic-rhetorical integration, which is more concentrated than in conventional advertising, constitutes the genre's distinctive adaptive response to short-video constraints. Theoretically, the study extends speech act classification to the underexplored domain of affiliate marketing discourse. The findings offer a structured framework for analyzing persuasive language in digital media, with potential applications in educational contexts where critical digital literacy is emphasized.